People's knowledge, attitudes, practice, and healthcare education demand regarding OSA: a cross-sectional study among Chinese general populations - Pan, Zhongjing; Ma, Tianpei; Zeng, Qinghan; Xu, Ting; Ran, Qiong; Li, Tianming; Lu, Dan (Frontiers in Public Health, 2023)
Background Population knowledge and attitudes toward obstructive sleep apnea (OSA) syndrome are critical to public health initiatives to overcome the disease. Healthcare education is an appropriate approach to expediting the process to build active medical practice models in the public. Objective This study aimed to assess the level of knowledge, attitude, and practice (KAP) regarding OSA and healthcare education demand among the Chinese general population. Methods A cross-sectional survey was performed online via Wenjuanxing in China between 8 February and 8 March 2022, using a 34-item questionnaire designed and reviewed by multidisciplinary experts. Results This study enrolled 1507 respondents, aged 18 to 68, with a city-to-countryside ratio of approximately 2:1. Four-fifths of respondents reported that they had children (n = 1237), and mothers accounted for 57.7%. If they or their children had symptoms of OSA, nearly nine in 10 respondents would undertake positive medical practices, especially parents. A total of 89.4% of the respondents reported a desire to receive healthcare education through the new multimedia approach, and most were concerned about the etiology of OSA. Conclusion The current study indicated that even the higher educated and urban populations in China had insufficient knowledge about positive attitudes toward and practices regarding OSA, indicating an urgent demand for healthcare education. A special emphasis should be placed on appropriating population demand for healthcare education and promoting the benefits of active medical practice models in sleep medicine.